PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 002 JUMRAH KECAMATAN RIMBA MELINTANG - Enrita Sihotang; Hendri Marhadi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The Research background is lowering of learning ipa of student of class III SDN 002 Jumrah, on the class average 57,08, mean while the minimal completeness criterion is 70. Among 24 students, there were only 6 students’ were able to achieve the minimal completeness criterion. the research was classroom action research (CAR ) which was done to increase the students’ learning out come on science in the student III grade of SDN 002 Jumrah used cooperative learning model namely Two Stay Two Stray ( TSTS ). The instruments of collecting data in this scientific writing are teacher and students’ activities sheet as well the learning outcome. The scientific writing seved datas of students’ learning outcome before action 57,08 rose to 12,92% become 70 in the first cycle. in the second cycle was higher 25% on the average 82,08%. The teacher’s activities in the first cycle of the first meeting obtained 58,33% with enough catagory. In the second meeting was 75% higher than before with good catagory. And than, in the second cycle of the first meeting the teacher’s activities increased in the percentage of 79,17% with good catagory. And in the second cycle of the second meeting was 91,67% with very good catagory. The students’activities in the first cycle of the first meeting got percentage as many 54,17% with enough catagory. In the second meeting was 70,83% with good catagory in the cycle students’ had understood about the implementation of cooperative learning model TSTS tipe which known by the percentage of student activities in the second cycle of the first meeting was 75% with good catagory. In the second meeting of the cecond cycle the percentage was 87,5% with very good catagory. The result of the research in the third grade proved that the implementation of cooperative learning model TSTS type can increase the students’ learning outcome on science in the third grade.Key words : cooperative learning model TSTS type the result of science studies